DNA and Histone Methylation as Cancer Targets - Kaneda, Atsushi; Tsukada, Yu-ichi (Springer International Publishing : Imprint: Humana Press, 2017)
This book will focus on DNA and histone methylation in epigenetics and describe how it is involved in the molecular mechanisms responsible for the development of cancer. Chapters will summarize the current knowledge of the molecular basis of DNA and histone methylation and explain how it is involved in cancer, describe the features of DNA and histone methylation associated with particular types of cancer, diagnostic/therapeutic applications, and future directions of DNA and histone methylation as cancer targets.
Keywords: Medicine.; Cancer research.; elektronické knihy; electronic books